It is time to implement prepump arterial pressure monitoring during hemodialysis: A retrospective multicenter study. Issue 6 (November 2020) - Sun, Chun-Yan; Mo, Ya-Wen; Lan, Li-Juan; Han, Xiao-Wei; Song, Li; Zhang, Guan-Rong; Zhou, Li-Fang; Zheng, Shu-Qian; Chen, Ying-Gui; Liu, Shuang-Xin; Liang, Xin-Ling; Fu, Xia
Introduction: Prepump arterial pressure (Pa) indicates the ease or difficulty with which the blood pump can draw blood from vascular access (inflow) during hemodialysis. The absolute prepump arterial pressure to blood pump speed (Qb) ratio (|Pa/Qb|) may reflect the dysfunction of other vascular accesses. There is no consensus on the impact of |Pa/Qb| on arteriovenous fistula dysfunction. This study aimed to demonstrate the impact of |Pa/Qb| on arteriovenous fistula dysfunction. Methods: In this retrospective analysis, 490 hemodialysis patients with arteriovenous fistula from three hospitals were enrolled. Data were extracted from the I-Diapro database and hospital case systems. The absolute values for |Pa/Qb| and other data collected in the first month of enrollment were used to predict arteriovenous fistula dysfunction and determine the |Pa/Qb| cutoff value. Based on this value, patients were grouped, and 1-year arteriovenous fistula function was analyzed. Patients were followed until arteriovenous fistula dysfunction, until access type replacement, or for 12 months. Results: The area under the receiver operating characteristic curve for fistula dysfunction over 1 year was 0.65, with an optimal |Pa/Qb| value, sensitivity, and specificity of 0.499, 60.7%, and 72.6%, respectively. |Pa/Qb| > 0.499 was associated with earlier intervention (317.37 ± 7.68 vs 345.96 ± 3.64 days), lower survival ( p  < 0.001), and a 3.26-fold greater risk of arteriovenous fistula dysfunction ( p  < 0.001) than |Pa/Qb| ⩽ 0.499. Conclusions: |Pa/Qb| was an independent risk factor for arteriovenous fistula dysfunction. Nurses should emphasize |Pa/Qb| monitoring and properly set blood pump speed according to this ratio to protect arteriovenous fistula function. |Pa/Qb| > 0.499 might be a predictive measure of arteriovenous fistula dysfunction.